MORPHOSYNTACTIC FEATURES OF THE AMAZONian SPANISH ON BILINGUAL INDIGENOUS SPEAKERS IN LIMA* - Falcon, Pedro (2012)
From a functional sociolinguistic perspective, this paper analyzes and describesthe most recurrent morphosyntactic features of the Spanish produced by bilingualindigenous peoples –Shipibo and Asháninka speakers– living in MetropolitanLima. It evaluates and explains the order of constituents, elision, insertion,concordance, morphosyntactic processes, wordformation and reduplication. It isworth mentioning that the morphosyntactic characteristics of this sector of thepopulation, show linguistic forms that reproduce the structures of their mothertongues and a marked influence of Andean Spanish, product of a fluid relationship,mostly with the Ashaninka population.